Cefaleas - Silva R., Carlos; Venegas F., Pablo (Revista Hospital Clínico Universidad de Chile, 2009)
Headache is the most frequent symptom that makes patients to attend a neurologist’s office. Is a very common reason to attend general physician as well, so is very important to know how to do a correct diagnosis between primary and secondary headache and to treat the most frequent ones. This review includes migraine, tension type headache and others, from a clinical perspective, with special focuses on clinical clues that allow clinicians a more specific diagnosis and treatment. We want to emphasize how rational treatment should be prescribed and how to avoid rebound headache and others complications related to certain drugs, in particularergotamines.